Improving Cross-cultural "Mind-reading" with Electrical Brain Stimulation. (10th February 2021) - Martin, A.K.; Su, P.; Meinzer, M.
Highlights: Cross-cultural difference demonstrated for Reading the Mind in the Eyes (RMET). RMET Performance correlated with cross-cultural contact. Anodal stimulation to the dmPFC improved performance, especially in those with less cross-cultural contact. Abstract: A cross-cultural disadvantage exists when inferring the mental state of others, which may be detrimental for individuals acting in an increasingly globalized world. The dorsomedial prefrontal cortex (dmPFC) is a key hub of the social brain involved in ToM. We explored whether facilitation of dmPFC function by focal high-definition tDCS can improve cross-cultural mind-reading. 52 (26 F/M) Singaporeans performed the Caucasian version of the Reading the Mind in the Eyes Test (RMET) and received HD-tDCS to either the dmPFC or a control site (right temporoparietal junction, rTPJ) in sham-controlled, double-blinded, crossover studies. Contact with Caucasians was determined for the Singaporean cohort as a potential mediator of RMET performance and HD-tDCS response. 52 Caucasians completed the RMET during sham-tDCS and served as a comparison group. A cross-cultural disadvantage on the RMET was confirmed in the Singaporean cohort and this disadvantage was more pronounced in those participants who had less contact with Caucasians. Importantly, HD-tDCS to the dmPFC improved RMET performance in those with less contact. No effect was identified for rTPJ HD-tDCS or for the age/sex control task demonstrating task and site specificity of the stimulation effects. Electrical stimulation of the dmPFC selectively improves the rate of cross-cultural ToM inference from facial cues, effectively removing cross-cultural disadvantage that was found in individuals with lower cross-cultural exposure.